A Survey of Perceptually Motivated 3D Visualization of Medical Image Data. (4th July 2016) - Preim, Bernhard; Baer, Alexandra; Cunningham, Douglas; Isenberg, Tobias; Ropinski, Timo
Abstract: This survey provides an overview of perceptually motivated techniques for the visualization of medical image data, including physics‐based lighting techniques as well as illustrative rendering that incorporate spatial depth and shape cues. Additionally, we discuss evaluations that were conducted in order to study the perceptual effects of these visualization techniques as compared to conventional techniques. These evaluations assessed depth and shape perception with depth judgment, orientation matching, and related tasks. This overview of existing techniques and their evaluation serves as a basis for defining the evaluation process of medical visualizations and to discuss a research agenda.